Analisis Manajemen Pengadaan Barang/Jasa di Kantor Balai Penelitian dan Pengembangan Kesehatan Donggala - Muhammad Irham S; Slamet Riadi; M Nur Alamsyah (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Procurement of goods and services is a fundamental part of good governance. Various problems occur in the procurement of goods and services, such as not optimizing the quality of budget planning and procurement, not understanding the consequences of each authority, and not creating coordination between users and providers. This study aims to analyze the management of procurement of goods/services at Donggala Health Research and Development Center. The method used is purposive sampling, with Milles Hubermen and Saldana analysis approach technique. Data were collected through observation, interview and documentation. The results showed that the management of goods / services procurement at Donggala Health Research and Development Center has not run optimally because the planning indicator has not run well due to budget constraints, and one of the organizing sub-indicators, namely coordination between Donggala Health Research and Development Center and PT, CV, Firm or Cooperative has not been carried out properly, but the organizing, actuating, controlling indicators have run well.